Environmental impacts caused by the burning of sugar cane in Laredo-Trujillo - Pablo Carrera, Juan (2010)
This paper is a summary of a thesis to get the professional title of Geographical Engineer. The burning of sugar cane is the major source of pollution in the district of Laredo and surrounding areas. This burning is done before harvest where the leaves are burned, it is done to ensure control of pests and reduce harvesting costs, while the one made after the harvest which is burned in the bag of the cane and the remaining green leaves can eliminate waste and accelerate land preparation and replanting. When cane burning is taking place, pollution occurs in form of shower of particles and fly ash together with no visible smoke and gases. Those most affected are housewives, dirty as these fly ash floors, household goods and clothes placed on clotheslines.